Hyaluronic Acid Inhibits Polycation Induced Cellular Responses - A. lalenti; A. lanaro; G. Brignola; P. Marotta; M. Di Rosa (Hindawi Limited, 1994)
Positively charged macromolecules cause a variety of pathological events through their electrostatic interaction with anionic sites present on the membrane of target cells. In the present study we have investigated the effect of hyaluronic acid, a negatively charged molecule, on rat paw oedema induced by poly-L-lysine as well as on histamine release from rat mast cells and nitric oxide formation from rabbit aorta, both induced by this polycation. The results indicate that hyaluronic acid is able to suppress these poly-L-lysine induced effects with a mechanism which possibly depends on its negative charges which may balance the effects of positively charged polycations.